Pengaruh Current Ratio Dan Debt To Equity Ratio Terhadap Return On Assets Sebelum Dan Selama Pandemi COVID-19 Pada Perusahaan Sektor Perdagangan, Jasa, Dan Investasi Yang Terdaftar Di ISSI - Ash Shidqi, Muhammad Irsyad; Djuwarsa, Tjetjep; Hadiani, Fatmi; Syarief, M. Edman (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This study examines the relationship between the company's financial ratios, namely Current Ratio and Debt to Equity Ratio as independent variables to Return On Assets which are the dependent variable in companies in the Trade, Services and Investment sectors. This study uses company panel data for 2017-2021 based on the three years before and two years during the COVID-19 pandemic. COVID-19 is a moderating variable that strengthens or weakens the relationship between CR and DER on ROA. The study population is 102 trade, service and investment business sectors listed on the Indonesian Sharia Stock Index. Based on random sampling, 26 companies were obtained as samples. The results obtained show that CR, both moderated by COVID-19 and without being moderated, does not affect the ROA of the business sector. Meanwhile, DER results without being moderated by COVID-19 negatively and significantly affect ROA, then DER moderated by COVID-19 positively and significantly affects ROA. The positive relationship obtained by DER on ROA during COVID-19 is interpreted as a quasi moderator, where COVID-19 as a pseudo moderating variable is able to interact with DER thereby strengthening its negative effect on company ROA.